2008
DOI: 10.1159/000151701
|View full text |Cite
|
Sign up to set email alerts
|

Independent Role of Hypertension in Bell’s Palsy: A Case-Control Study

Abstract: Background/Aim: In this case-control study, our aim was to check for a possible independent role of hypertension in increasing the risk of developing Bell’s palsy. Methods: All patients diagnosed as having Bell’s palsy referred to a neurology clinic were enrolled as cases. Controls were selected among other patients referred to the same clinic. Data were analyzed using the Stata 8 statistical software package. To detect the independent effect of exposure variables, a multiple logistic regression test was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
3
43
0
1
Order By: Relevance
“…Since Korczyn [4] first reported a high frequency (66%) of diabetes mellitus (DM) in patients presenting with BP, this association has been confirmed by several researchers, most recently by Savadi-Oskouei et al [5] (prevalence of DM: 29%, the same as above). Researchers have also reported that the incidence of hypertension in patients with BP was higher than in control groups.…”
Section: Discussionmentioning
confidence: 66%
“…Since Korczyn [4] first reported a high frequency (66%) of diabetes mellitus (DM) in patients presenting with BP, this association has been confirmed by several researchers, most recently by Savadi-Oskouei et al [5] (prevalence of DM: 29%, the same as above). Researchers have also reported that the incidence of hypertension in patients with BP was higher than in control groups.…”
Section: Discussionmentioning
confidence: 66%
“…There are several possible risk factors for BP, including severe preeclampsia [71], psychological factors [72], glucose metabolism abnormalities [73], radiation exposure [74], hypertension [75], and migraine [76]. Recently, epidemiological studies have revealed that the incidence of BP is also related to extreme temperature exposure.…”
Section: Acute Cold Exposurementioning
confidence: 99%
“…In Korea, approximately 0.057% of the population is diagnosed annually with Bell's palsy 3 . The incidence of Bell's palsy is not different between the sexes and covers all age populations, with the peak incidence observed in the population aged 15-50 years old 4,5 . Because it is diagnosed by exclusion of other organic causes, the exact pathophysiologic causes of Bell's palsy remain unknown.…”
mentioning
confidence: 93%